2018
DOI: 10.3390/s18092939
|View full text |Cite
|
Sign up to set email alerts
|

On the Effects of InSAR Temporal Decorrelation and Its Implications for Land Cover Classification: The Case of the Ocean-Reclaimed Lands of the Shanghai Megacity

Abstract: In this work, we focused on the ocean-reclaimed lands of the Shanghai coastal region and we evidenced how, over these areas, the interferometric synthetic aperture radar (InSAR) coherence maps exhibit peculiar behavior. In particular, by analyzing a sequence of Sentinel-1 SAR InSAR coherence maps, we found a significant coherence loss over time in correspondence to the ocean-reclaimed platforms that are substantially different from the coherence loss experienced in naturally-formed regions with the same type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…The MQQA method has been proposed to combine time overlapped DInSAR deformation time series derived by different SAR instruments. The performance of the MQQA method has been tested by considering the deformation measurements related to five levelling benchmarks, with results supporting [27]).…”
Section: Generation Of Long-term Insar Ground Displacement Time-series Through a Novel Multi-sensor Data Merging Techniquementioning
confidence: 81%
See 3 more Smart Citations
“…The MQQA method has been proposed to combine time overlapped DInSAR deformation time series derived by different SAR instruments. The performance of the MQQA method has been tested by considering the deformation measurements related to five levelling benchmarks, with results supporting [27]).…”
Section: Generation Of Long-term Insar Ground Displacement Time-series Through a Novel Multi-sensor Data Merging Techniquementioning
confidence: 81%
“…Details on this research study and further insights on the achieved results can be found [27]. [27]).…”
Section: Research Approachmentioning
confidence: 98%
See 2 more Smart Citations
“…γ temporal is temporal decorrelation, γ geom is geometric decorrelation, γ vol is the volumetric scattering decorrelation, these three factors matter in our study. Temporal decorrelation is caused by surface changes between SAR acquisitions [48,49]. In this study, the excavation of open-pit mines changes the reflection characteristics of ground objects over a short time period, thereby introducing decorrelation.…”
Section: Coherence and Decorrelationmentioning
confidence: 99%